Cost-Effectiveness of Poly ADP-Ribose Polymerase Inhibitors in Cancer Treatment: A Systematic Review - Chan, Vivien Kin Yi; Yang, Runqing; Wong, Ian Chi Kei; Li, Xue (Frontiers in Pharmacology, 2022)
Background: PARP inhibitors have shown significant improvement in progression-free survival, but their costs cast a considerable financial burden. In line with value-based oncology, it is important to evaluate whether drug prices justify the outcomes. Objectives: To systematically evaluate PARP inhibitors on 1) cost-effectiveness against standard care, 2) impact on cost-effectiveness upon stratification for genetic characteristics, and 3) identify factors determining their cost-effectiveness, in four cancer types. Methods: We systematically searched PubMed, EMBASE, Web of Science, Cochrane Library using designated search terms, updated to 31 August 2021. Trial-based or modelling cost-effectiveness analyses of four FDA-approved PARP inhibitors were eligible. Other studies known to authors were included. Reference lists of selected articles were screened. Eligible studies were assessed for methodological and reporting quality before review. Results: A total of 20 original articles proceeded to final review. PARP inhibitors were not cost-effective as recurrence maintenance in advanced ovarian cancer despite improved performance upon genetic stratification. Cost-effectiveness was achieved when moved to upfront maintenance in a new diagnosis setting. Limited evidence indicated non-cost-effectiveness in metastatic breast cancer, mixed conclusions in metastatic pancreatic cancer, and cost-effectiveness in metastatic prostate cancer. Stratification by genetic testing displayed an effect on cost-effectiveness given the plummeting ICER values when compared to the ‘treat-all’ strategy. Drug cost was a strong determinant for cost-effectiveness in most models. Conclusions: In advanced ovarian cancer, drug use should be prioritised for upfront maintenance, and for patients with BRCA mutation or BRCAness at recurrence. Additional economic evaluations are anticipated for novel indications.